KRITIK TERHADAP PAHAM FIDEISME DAN SEKULARISME TENTANG PENGGUNAAN IMAN DAN PIKIRAN - Gidion (Vox Dei: Jurnal Teologi dan Pastoral, 2020)
This paper specifically presents a critique of the conflicting ideas of Fideism and Secularism about the use of faith and thought. Indications of the debate between the mind devotees and the faith devotees, appears until now. There are groups who believe that the Word is received only by faith and does not require the mind roles. The mind is seen as an obstacle in receiving God's Word. There are also groups who believe that all the true Word is the Word that makes sense. Things that are supernatural or unacceptable to logic, are seen as unimportant. This paper aims to provide a critique of the views of Fideism and Secularism, which contradict each other in the use of mind and faith. This paper also aims to show the relationship between mind and faith. The method used in this study is the study of literature, and the study of theological meaning about mind and faith to find the relationship between mind and faith.